Estudo dos danos morfofuncionais causados pela criopreservação no sêmen de tatu-peba,Euphractus sexcinctus Wagler, 1830 - Sousa, Patrícia da Cunha (2013)
The objective of this work, cryopreserve semen from six-banded armadillos, assessing in advance the effects of centrifugation and dilution of their seminal parameters over thermoresistance test (TRT) in order to define the best diluent to be used in semen cryopreservation of this species. Semen samples (n = 12) derived from 04 adult males collected by electroejaculation were divided into four aliquots, two immediately diluted in Tris or powdered coconut water (ACP-119®), and the other centrifuged (800g/10 min) prior to dilution. The samples were incubated at 34°C for 3h and the seminal parameters evaluated at intervals of 1 h. In general, was observed greater efficiency of Tris regard to the preservation of seminal parameters along the TRT, especially up to 120 min of evaluation, but after this period the two extenders were equivalents. Still, the centrifugation caused deleterious effect on semen quality of six-banded armadillos, this method is not suitable for this species. For the cryopreservation of the semen of six banded armadillos, was then diluted in Tris-base, plus 20% egg yolk and 3% glycerol. Following the steps of dilution, the samples semen cooling and thawing was performed classical analysis simultaneously to fluorescence analysis, employing the combination of fluorophores to assess the plasma membrane integrity (Propidium iodide - PI and Hoechst - H-342), and also mitochondrial activity (CMXRos - Mito Tracker red®). Most of the changes observed in all stages of cryopreservation of semen of six-banded armadillos was secondary, but the proportions of these defects increased significantly from step cooling, and higher in step thawing, due to the impacts of heat shock and osmotic stress be more significant in this phase. The results of fluorescence analysis indicated a percentage of cells with intact plasma membrane more higher (8.4%) than that of motile cells (6.1%) on thawed semen. This may be due to the action of egg yolk, to provide greater structural integrity to some cells. In images taken by transmission electron microscopy were identified in sperm cryopreserved rupture and vesiculation of the plasma membrane, mitochondrial abnormalities, as well nuclear and acrosomal changes characterized by changes in chromatin and sperm capacitation, respectively. This study is the first report on the use of cryopreservation on semen xenarthras, and given the importance of biotech to preserve the genetic material of armadillos, the results obtained here are fundamental to promote the improvement of semen cryopreservation in six-banded armadillos, aiming its applications in other species of armadillos endangered or vulnerable to extinction